Are the teams sports soccer, futsal and beach soccer similar? - Leite, W.; Barreira, D. (International Journal of Sports Science, 2014)
Soccer, Futsal and Beach Soccer are classified as team sports of invasion, thus having common characteristics. The aim of this study is: (i) to analyze the evolutionary trends concerning to the average number of goals per game and per competition; (ii) to analyze the incidence of goals regarding the periods of play they tend to occur; and (iii) to scrutinize the influence of scoring first a goal in a match on the respective final result. We analyzed Soccer (n=836), Futsal (n=306) and Beach Soccer (n=148) matches played in World Cup tournaments, organized by the Fédération Internationale de Football Association (FIFA), performing a total of 1290 matches. It was found that the average number of goals per game obtained in FIFA World Cups, as both Soccer and Beach Soccer, evidenced a marked tendency to decrease, while for Futsal game it was verified the opposite. Regarding the timing of the goals, in the three team sports it was found that the majority of goals were scored in the last period of the game (Soccer: 19.42%; Futsal: 36.25%; Beach Soccer: 37.21%). Examining the influence of scoring the first goal in the final result of the match, in soccer and in Futsal it was found that the average probability of winning the game is approximately 70%, while in Beach Soccer it is about 60%. Thus, we suggest that the origin of the results for the analyzed variables is related to the interaction of physical, technical, tactical and psychological aspects, and the weighting of each one is different in relation to the specificity of the each team sports.